Investigating the Mediating Role of Self-Efficacy in the Relationship between Job Demand and Role Ambiguity with Employee Well-Being - Mahnaz Rahimi; Mohammad Hassani; Hasen Ghalavand (مدیریت بهره وری)
Abstract: Improving the well-being and support of employees will lead to the success of the organization because if the organization supports the employees, they will feel more committed to the organization and will work towards increasing performance and achieving the goals of the organization. Finding factors affecting employee well-being is essential and can help organizations to improve performance and achieve success. Hence, this research sought to test a model of causal factors affecting employee well-being with the mediation of self-efficacy among the employees of Razi University of Kermanshah. The method of the present research was practical in terms of its purpose and descriptive-survey in terms of data collection. The statistical population included all the employees of Razi University of Kermanshah, which were 490, 215 of whom were selected as a sample from different faculties using Morgan's table and stratified random sampling method. The findings showed that job demand and role ambiguity are effective on employees' well-being both directly and through the mediation of self-efficacy. According to the findings of the research, it can be concluded that excessive job demands and ambiguity in the role of employees can increase emotional exhaustion and reduce the work engagement of employees, which can decrease the well-being of employees.   Key Words: job demand, role ambiguity, well-being, self-efficacy, university     1.Introduction In this research, we aim to develop a model that identifies the factors affecting employees’ welfare since enhancing employee welfare and support can contribute to the success of the organization. When an organization supports the employees, they will feel more committed to the organization, which in turn leads to improved performance. This heightened performance ultimately contributes to the successful achievement of the organization's goals. Identifying effective factors that influence employees' well-being is essential and has helped organizations to improve their performance and achieve success. The purpose of this research is to investigate the effect of role ambiguity and job demands on employees' well-being with a focus on the mediation role of self-efficacy because role ambiguity arises from insufficient knowledge of goals and information. Role ambiguity has caused burnout and reduced work engagement among employees, and high job demands have also caused burnout and lack of work engagement among employees due to mental fatigue, leading to a decrease in well-being among them. 2.Literature Review Harter et al. (2003), in their research showed that people who do not know what the organization expects from them are more likely to have job conflicts and spend more time trying to understand what the organization expects from them, clarifying the ambiguity of their role, which has negative consequences for their well-being. Additionally, research shows that role ambiguity is related to a decrease in work engagement, which causes a decrease in employee well-being (Rives et al., 2011) and that job demands are related to emotional exhaustion and negativity is related to conflict. The research of Skalvik and Skalvik (2017) has shown that self-efficacy has a positive relationship with work engagement and a negative relationship with emotional exhaustion. 3.Methodology In this article, we intended to model the factors affecting employees' well-being with the mediation of self-efficacy using a quantitative approach and structural equation modeling. For this purpose, we first determined the independent, dependent and mediating variables based on the backgrounds. In this research, job demands and role ambiguity are the independent variables, employees’ wellbeing which includes dimensions of work engagement and emotional exhaustion, is the dependent variable and self-efficacy is the mediating variable. The data were collected using valid questionnaires and the sample was selected from the statistical population based on the Morgan's table. Due to the fact that the statistical population was heterogeneous and the employees were selected from different faculties, stratified random sampling method was used. 4.Result To obtain the results, we evaluated both internal and external models. The evaluation of the external model focused on the validity and reliability of the model, and the internal model evaluation examined the path coefficients, t-statistics and their significance in relation to model fit. In this research, the model had a good fit. The findings showed that job demands and role ambiguity are effective on employees' well-being both directly and through the mediation of self-efficacy, that is, with the increase of job demands and role ambiguity, emotional burnout increases, work engagement decreases, and as a result, employees' well-being decreases. Also, with the reduction of role ambiguity and job demands, emotional burnout decreases and work engagement increases as a result of which the level of employees’ well-being increases. 5.Conclusion The present study was an attempt to understand the employees’ well-being at work from an integrated perspective, which includes a positive dimension (work engagement) and a negative dimension (job burnout). By putting these two variables together, their relationship with well-being in the workplace can be understood. However, the level of employee involvement should be given equal consideration. According to the findings of this research, it seems that by reducing job demands and role ambiguity, the well-being of employees can be increased, which leads to an increase in employee productivity and ultimately the effectiveness and efficiency of the organization. Yet, when job demands are high, there is a lot of psychological pressure on the employees, and this psychological pressure manifests in an individual's behavior in the form of fatigue, stress and anger. In this situation, despite the mental and psychological pressures, the individual struggles to concentrate on his work, leading to superficial performance and insufficient time dedicated to his work and its improvement. Furthermore, in a situation where a person is uncertain about his role and unclear about the organization’s expectations because the evaluation of his performance that is carried out by his superiors is unclear to him, he is under psychological pressure, which eventually causes emotional fatigue. It is clear that due to role ambiguity, he is not able to get engaged in his work and this leads to a decrease in well-being.